THE RELEVANCE OF PHYSICAL EXERCISE IN POST-COVID RECOVERY - da Silva Conceição, Jhonny; Teixeira, Taner (Health and Society, 2023)
The relevance of physical exercise in post-COVID recovery consists of the importance of regular physical activity for individuals who have recovered from the disease caused by the coronavirus. During COVID-19 infection, many patients may face a variety of complications such as muscle weakness, fatigue, difficulty breathing, and cardiovascular problems. The literature review resulted in an analytical and critical text that exposed ideas from studies related to the topic. The study was based on scientific articles, theses, and books published between the years 2018 and 2023. In summary, the research highlights the importance of physical exercise in post-COVID recovery and emphasizes its benefits for both the physical and mental health of patients. The obtained results indicate that the benefits of exercise include improved lung function, reduced stress and anxiety, improved mood, and strengthened immune system. Therefore, it is understood that physical activity encourages individuals to include activities in their daily routines, tailored to their personal needs, in order to promote a more effective recovery for the patient, promoting quality of life and physical resilience